Halogen Bonding in the Complexes of Brominated Electrophiles with Chloride Anions: From a Weak Supramolecular Interaction to a Covalent Br–Cl Bond - Cody Loy; Matthias Zeller; Sergiy V. Rosokha (Crystals, 2020)
The wide-range variation of the strength of halogen bonds (XB) not only facilitates a variety of applications of this interaction, but it also allows examining the relation (and interconversion) between supramolecular and covalent bonding. Herein, the Br…Cl halogen bonding in a series of complexes of bromosubstituted electrophiles (R-Br) with chloride anions were examined via X-ray crystallographic and computational methods. Six co-crystals showing such bonding were prepared by evaporation of solutions of R-Br and tetra-n-propylammonium chloride or using Cl− anions released in the nucleophilic reaction of 1,4-diazabicyclo[2.2.2]octane with dichloromethane in the presence of R-Br. The co-crystal comprised networks formed by 3:3 or 2:2 halogen bonding between R-Br and Cl−, with the XB lengths varying from 3.0 Å to 3.25 Å. Analysis of the crystallographic database revealed examples of associations with substantially longer and shorter Br…Cl separations. DFT computations of an extended series of R–Br…Cl− complexes confirmed that the judicious choice of brominated electrophile allows varying halogen Br…Cl bond strength and length gradually from the values common for the weak intermolecular complexes to that approaching a fully developed covalent bond. This continuity of halogen bond strength in the experimental (solid-state) and calculated associations indicates a fundamental link between the covalent and supramolecular bonding.